Agriculture and the rural economy in Pakistan: Issues, outlooks, and policy priorities - Spielman, David J.; Malik, Sohail Jehangir; Dorosh, Paul A.; Ahmad, Nuzhat (University of Pennsylvania Press, 2016)
Historically, agriculture has been crucial to Pakistan’s economic growth and development and remains so even today. The sector employs almost half of the country’s labor force, supplies key inputs to the country’s manufacturing sector, generates a significant share of export earnings, and nourishes a rapidly growing population. Further, beyond agriculture is the wider rural economy, including nonfarm economic activities such as small enterprises, transport services, village retail shops, local schools, and clinics, all of which account for an estimated 40 to 57 percent of total rural household income.